(untitled) (Development Service Industry Management, 2024)
The article provides a comprehensive analysis of the main macroeconomic indicators of Ukraine for the period 2015–2023 under the influence of military actions, economic instability and external economic shocks. Key indicators of economic development are considered, in particular, GDP dynamics, inflation rate, public debt, volumes of foreign trade and investment activity. The authors focus on economic growth trends in crisis situations and post-crisis recovery processes. The impact of internal and external factors on the formation of the country’s economic stability is assessed. Particular attention is paid to the consequences of military actions, which significantly transformed the economic structure, reduced investment attractiveness and caused an increase in the burden on the state budget. The effectiveness of economic policy measures aimed at stabilizing the macroeconomic situation, restoring industrial potential and attracting foreign investment is analyzed. The article emphasizes the importance of adapting Ukraine’s economic strategy to modern challenges, in particular through economic diversification, the introduction of innovative technologies and integration into global markets. The main problems that hinder sustainable economic development are identified, including the instability of the financial sector, a significant level of public debt, a shortage of resources for restoring and maintaining economic security. The analysis allows us to better understand the features of macroeconomic processes in Ukraine, which is the basis for developing further strategic directions for development.